Miracle of Poetic Creations: Array - Balțatu, Ludmila (Journal of Danubian Studies and Research, 2020)
“Nature is a temple in which living pillars/ Sometimes give voice to confused words;/ Man passes there through forests of symbols/ Which look at him with understanding eyes”. These are the thoughts written down by the French poet Charle Baudelaire. At present it can be certainly reaffirmed that namely the symbol constitutes the key to the spiritual universe insight. In this context, I will remark the following: same to the great Danube, that has been being sung from the oldest times in folklore creations, represents a symbol. For Eminescu the Danube symbolizes the force of resistence of the Romanian nation on the invadors way. While Marin Sorescu, named the Danube “Its Majesty”, as this river expresses the glory of the nation, as well as the Romanian greatness and dignity. The present generations are very considerate as well to this river that flows along Europe, since, while referring to the Danube, we speak of the dialogue, of the indispensable reciprocity as the commercial relations have been kept on the Danube from ancient times.